RANCANG BANGUN SENSOR DETEKSI DINI KERUSAKAN BUSI PADA MESIN PEMBAKARAN DALAM BERBASIS MIKROKONTROLER ATMEGA 328 - Bagus Prasetyo Sadikin (2020)
At this technological advanced era, the technological development also rapidly evolving with this the need for information and monitoring of data from machinery also increasing, like a growing need for an engine to motorized our society we still rely on internal combustion engine in our daily lives, this engine typically uses internal combustion and one of the most important component of it is a spark plug, a spark plug is important in a combustion cycle, but there is not much research on detecting a spark plug failure on a typical engine. With all that being said a sensor that is capable of quickly detecting a spark plug failure, this type of maintenance is a corrective maintenance to increase a lifespan of other component and maintenance cost. This design and processes done with a design and basic operational concept of arduino IDE programming and with a bunch of induction system sensors to detect activity of a spark plug and detecting a failure happening in an engine while it operates. This early detection system use an induction system and converting analog signal into a digital logic level of 5V with using a main function of attachInterrupt in Arduino IDE program.